2017
DOI: 10.1007/s00408-017-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Malignant and Paramalignant Pleural Effusions by Combining Clinical, Radiological and Pleural Fluid Analytical Parameters

Abstract: The data herein suggest that the identified predictor values applied to tree diagrams, which required no extraordinary measures, have a higher rate of correct identification of malignant, paramalignant and benign effusions when compared to techniques available today and proved most useful for usual clinical practice. Future studies are still needed to further improve the classification of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Tumor markers and LDH are the important parameters to differentiate benign and malignant lesions, particularly when detected in pleural effusion, ascetic fluid, and pancreatic cystic fluid. 14,15,26 However, we did not consider mediastinal cyst fluid biochemical examinations in this study. Previous studies have shown that serum carbohydrate antigen 19-9 and CEA levels are only elevated in patients with benign mediastinal cysts; often an elevated CEA level indicates that the occupying lesions are cystic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tumor markers and LDH are the important parameters to differentiate benign and malignant lesions, particularly when detected in pleural effusion, ascetic fluid, and pancreatic cystic fluid. 14,15,26 However, we did not consider mediastinal cyst fluid biochemical examinations in this study. Previous studies have shown that serum carbohydrate antigen 19-9 and CEA levels are only elevated in patients with benign mediastinal cysts; often an elevated CEA level indicates that the occupying lesions are cystic.…”
Section: Discussionsupporting
confidence: 92%
“…Humoral fluid biochemical analysis is routinely applied in a clinical setting. Tumor markers and LDH are the important parameters to differentiate benign and malignant lesions, particularly when detected in pleural effusion, ascetic fluid, and pancreatic cystic fluid . However, we did not consider mediastinal cyst fluid biochemical examinations in this study.…”
Section: Discussionmentioning
confidence: 96%
“…In the literature, it has been reported that in cases with suspected cancer, if the malignant cell was not identified in the first cytological sample, repeated examination of the cytological mate-rial increases the likelihood of malignant neoplasm (1). However, since the contribution of repeated cytological samples to diagnosis is low, pleural biopsy is recommended in addition to the second cytological sampling (4). In another study, 44% of the first cytological samples of 414 patients were diagnosed with malignant cells, while 3 and more cytological samples obtained from all patients were found to contribute 6% to the diagnosis (15).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it may even be the first sign of a primary malignant tumor. Although the classification of PEs as transudates and exudates by clinical data makes a significant contribution to narrowing the differential diagnosis and organizing of subsequent examinations and treatments, the presence of malignant cells on cytology material is also important because of its association with cancer staging, prognosis, and survival (2)(3)(4). The main purpose of this method is to detect the presence of malignant cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation